Prompt and non-prompt J/ψ production in pp collisions at √s =7 TeV - Khachatryan, V. (2011)
The production of J/ψ mesons is studied in pp collisions at √s = 7 TeV with the CMS experiment at the LHC. The measurement is based on a dimuon sample corresponding to an integrated luminosity of 314 nb-1. The J/ψ differential cross section is determined, as a function of the J/ψ transverse momentum, in three rapidity ranges. A fit to the decay length distribution is used to separate the prompt from the non-prompt (b hadron to J/ψ) component. Integrated over J/ψ transverse momentum from 6.5 to 30 GeV/c and over rapidity in the range pipeypipe < 2.4, the measured cross sections, times the dimuon decay branching fraction, are 70.9 ± 2.1(stat.) ± 3.0(syst.) ± 7.8(luminosity) nb for prompt J/ψ mesons assuming unpolarized production and 26.0 ± 1.4(stat.) ± 1.6(syst.) ± 2.9(luminosity) nb for J/ψ mesons from b-hadron decays. © CERN for the benefit of the CMS collaboration 2011.